2003
DOI: 10.1021/cm0210795
|View full text |Cite
|
Sign up to set email alerts
|

Electrospinning and Stabilization of Fully Hydrolyzed Poly(Vinyl Alcohol) Fibers

Abstract: Fully (99+ %) hydrolyzed poly(vinyl alcohol) (PVA) was electrospun from water using Triton X-100 surfactant to lower the surface tension. The diameter of the electrospun PVA fibers ranged from 100 to 700 nm. Treatment of the PVA fiber mats with methanol for 8 h stabilized the fibers against disintegration in contact with water. In addition, the mats showed increased mechanical strength due to increased crystallinity following post-spinning treatment with methanol. We suggest that methanol treatment serves to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
223
2
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(249 citation statements)
references
References 18 publications
9
223
2
5
Order By: Relevance
“…The surface tension of aqueous PVA solutions exhibits a marked dependence on the DH of the PVA, which may result in an altered spinnability. For instance, Wnek and colleagues 14 reported that the addition of small amounts of Triton surfactant improves the electrospinnability of fully (499%) hydrolyzed PVA, probably because of lowered surface tension and retarded PVA gelation, and therefore affords reproducible electrospinning. Figure 1 (top) shows SEM images of PVA fibers electrospun from the solution with various DH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface tension of aqueous PVA solutions exhibits a marked dependence on the DH of the PVA, which may result in an altered spinnability. For instance, Wnek and colleagues 14 reported that the addition of small amounts of Triton surfactant improves the electrospinnability of fully (499%) hydrolyzed PVA, probably because of lowered surface tension and retarded PVA gelation, and therefore affords reproducible electrospinning. Figure 1 (top) shows SEM images of PVA fibers electrospun from the solution with various DH.…”
Section: Resultsmentioning
confidence: 99%
“…Depending on the rheological characteristics of the solution, electrospinning of a polymer solution can produce a variety of structures, mostly including beads, beaded fibers and fibers. 9,10 Various solution parameters affecting the morphology and diameter of electrospun PVA fibers, such as the solution concentration, molecular weight, 11 pH, 12 salt, 13 surfactant molecules 14 and so on, have been investigated. However, the effect of DH on the morphology and diameter of electrospun PVA fibers has been less studied.…”
Section: Introductionmentioning
confidence: 99%
“…2 PVA is widely used in textile, adhesive, cosmetic, food, drug, paper, and packaging industries. The main functional uses of PVA include filtration, catalysis, 5,6 membranes, optics, drug release, 7,8 enzyme mobilization, 8 tissue engineering, 9 among others. 10 Many of the key properties of PVA, such as those mentioned above, are the result of its significant cohesive energy due to its polarity from hydroxyl groups.…”
Section: Introductionmentioning
confidence: 99%
“…There are several studies demonstrating cross-linking of electrospun PVA membranes and their water stabilization. [4][5][6][7][8][9] Three major cross-linking methods have been described in the literature but each of these methods has its own problems in scaling up and cross-linking efficiency.(i) Immersion of electrospun membranes into an organic solvent (ii) Exposure of electrospun membranes to reagent vapor (iii) Addition of a cross-linker/catalyst to electrospinning solutionsThe first approach involving the use of an organic solvent is the simplest approach. Solvents such as Polyvinyl alcohol (PVA) is a water soluble polymer that requires further treatment to be stabilized before it can be used in aqueous environments.…”
mentioning
confidence: 99%